Does the moon cycle affect the physical endurance, balance, reaction-time, mood state and well-being in trained athletes? - Yousfi, N.; Arbi, M. M.; Kasmi, S.; Tabben, M.; Haddad, M.; Hammami, A.; Chaouachi, A.; Chamari, K. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Fascination with the moon has spanned millennia. It has recently been asserted that the moon cycle affects endurance performance in untrained individuals. The present study aimed at investigating the effects of the lunar cycle on intermittent endurance physical performance, balance and reaction-time capabilities, and selected physiological and psychological parameters in trained athletes. METHODS: Twelve male Taekwondo athletes (age, 22.3±0.8 years; height, 178.8±6.5 cm; body mass, 72.75±7.28 kg; %body fat, 13.9±3.6%) performed the Yo-Yo intermittent recovery test level-1 (YYIRT), the Y-balance test (YBT), and a reaction-time test (RT) during different lunar cycle phases (new moon (NM), full moon (FM), and half-moon). Participants` psychological profiles and well-being indices (i.e. a profile of mood state (POMS) and Hooper Index) were also taken during each moon phase. The testing sessions during the different moon phases were performed in a counterbalanced order. The tests order remained the same (POMS, then Hooper index, RT, YBT, YYIRT and rating of perceived exertion scale (RPE)), and all sessions were performed at noon (11:00 to 13:00 h) during the first day of each evaluated lunar phase. RESULTS: Analysis of variance tests showed that no significant differences were found between the three moon phases in all analyzed variables. CONCLUSIONS: This study showed that the different lunar cycle phases did not have significant effects on the selected physical performances and psychological indices in trained athletes.